POST-FRACTURING TREATMENTS DESIGN TO REDRESS THE DAMAGE CAUSED BY FRACTURING FLUID POLYMERS - Fabián-Alfredo Carrascal-Delgado; Zarith del Pilar Pachón-Contreras; Daniel-Ricardo Molina-Velasco (CT&F Ciencia, Tecnología & Futuro, 2014)
Seven chemical products with different chemical properties were evaluated as post-fracturing treatments to remove the polymer retained in the pore system of the fracture and adjacent rock after hydraulic fracturing. Three of those chemical products were used for the first time to degrade the polymer in fracturing fluids. All laboratory tests were conducted under the Unit K-1 Chichimene oil-field conditions - located in Eastern Colombia, and operated by Ecopetrol S.A. Fluid-fluid and fluid-rock compatibility tests were performed. In order to evaluate the capacity of the post-fracturing treatments to degrade the polymer in the fracturing fluid, a new methodology for polymer quantification was implemented. The chemical and thermal stability of the post-fracturing treatments was assessed trough coreflooding experiments. Finally, the evaluations of the effectiveness of the post-fracturing treatments were performed and assessed with coreflooding experiments using fractured rocks as porous media. The coreflooding results showed that the post-fracturing treatments evaluated promoted the recovery of about 40% of the total polymer retained in the porous system, and improved the retained permeability in values between 50 and 180%. The best obtained results came from the first-time usage of chemical products as post-fracturing treatments.